A CRITICAL ANALYSIS OF THE MANAGEMENT PROTOCOLS FOR IDIOPATHIC SUDDEN SENSORI-NEURAL HEARING LOSS. - Shah, Shahid A.; Karim, Asif; Ghani, Rehman (Journal of Ayub Medical College Abbottabad, 2004)
Background: Sudden sensori-neural hearing loss (SSNHL) is a clinical dilemma with great diversity in presentation and poorly understood pathogenesis and hence no definitive treatment protocol as yet. Both sexes are affected, middle age to elderly being the commonest age group. A variety of causes have been implicated as responsible for this condition, but most of the times it is difficult to isolate one, and hence most of the times a battery of investigations proves to be a clinical exercise. A number of treatment protocols have been suggested and used over the years, based on presumed etiological theories, claiming varying degrees of success. Methods: Relevant literature available on the net regarding the management and the efficacy of various treatment regimens for ISSNHL was critically analyzed by the authors (who are professorial staff of a medical college and consultants of a teaching hospital) to develop a consensus and recommendations on the most appropriate protocol. Results: It was asserted that various treatment regimens have not proved beyond doubt to be superior to one another or spontaneous recovery rates. Conclusion: SSNHL is a medical emergency that entails thorough investigations to search for a possible cause and institution of appropriate therapy. Failing identifying a cause, i.e idiopathic group, combination therapy with steroids and antiviral drugs could prove beneficial provided treatment is instituted early. A number of placebo controlled trials consuming various modalities are needed to determine an optimal treatment of ISSNHL. Psychological and psychiatric assistance has a certain role and so has the rehabilitation in the management of these patients. Key words: Deafness, Sensori-neural hearing loss, idiopathic, Management.